Effect of thermal drying on the physico-chemical and microbiological characteristics of drinking water treatment sludge - Juscimara Rodrigues Silva; Magda Hirsch de Carvalho; Amanda Maria Dantas de Jesus; Fabiana Alves Fiore (Cleaner Engineering and Technology)
The proper management and handling of drinking water treatment sludge (DWTS) is complex due to the quantity of sludge generated after treatment, the composition of the sludge, and the need to dry the material before its beneficial use or final disposal. Studies on the drying and feasibility of beneficial use of DWTS have been carried out on a laboratory scale, but few real-life applications have been proposed. This applied research is aimed at evaluating the effects of full-scale thermal drying on the physicochemical and microbiological characteristics of DWTS produced in Drinking Water Treatment Plants (DWTP), during two different climatic seasons (dry and rainy). For this purpose, the thermal drying process was described, and an exploratory analysis of the characteristics of the sludge before and after thermal drying was performed. Analyses were carried out on raw mass and on leached and solubilized extracts of DWTS samples, considering the Brazilian standard and the US standard for characterizing the risks to human and environmental health of waste. The results showed that the thermal drying process provided a reduction in the moisture content of DWTS of 62 % in the dry period and 74 % in the rainy season. It was also observed that thermal drying leads to the inactivation of microorganisms and that the resulting product brings benefits to the other stages of managing this waste. Furthermore, it also showed that the centrifuged sludges can be classified as non-hazardous and non-inert waste if the results of the analyses carried out on dry mass and solubilized extracts are considered. However, the presence of the elements: barium, chromium, and mercury, in the leached extracts, highlights the need for complementary toxicity testing for the proper classification of these wastes.